Tinjauan Bibliometrik: Tren Perkembangan Penelitian Terkait Analisis Kebutuhan Pelatihan (1984-2024) - Wibowo, Teguh Solih Setiyo; Widyatami, Kania; Pratminingsih, Sri Astuti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to identify publications on Training Needs Analysis (TNA) through interesting data visualization. The source of SCOPUS meta data was collected from publications in the form of the keyword 'Training Needs Analysis'. The database obtained was then analyzed and visualized using the bibliometrix package in R Software. The results of the analysis were interpreted based on performance analysis of citation and publication metrics, and science mapping based on co-citation, co-word analysis and also bibliographic coupling analysis. A total of 276 publications were selected following the research criteria in the period 1984 to 2024. The results of the study show that countries with English as the language of instruction still dominate the number of scientific publications, including several authors who are the most influential on the theme of Training Needs Analysis (TNA). The latest publication trends also show an increase in interest in research related to TNA with a high level of collaboration, both between authors and internationally, indicating that this topic attracts attention across disciplines and geographic regions. The relevance of the research to the development of theory and practice is seen from the high average citations and the use of modern analytical technology contained in keywords and collaborations, from initially focusing on health training expanding to general training management and then returning to mental health based on 3 analysis time spans.